2021
DOI: 10.3390/microorganisms9081733
|View full text |Cite
|
Sign up to set email alerts
|

Species of Dickeya and Pectobacterium Isolated during an Outbreak of Blackleg and Soft Rot of Potato in Northeastern and North Central United States

Abstract: An outbreak of bacterial soft rot and blackleg of potato has occurred since 2014 with the epicenter being in the northeastern region of the United States. Multiple species of Pectobacterium and Dickeya are causal agents, resulting in losses to commercial and seed potato production over the past decade in the Northeastern and North Central United States. To clarify the pathogen present at the outset of the epidemic in 2015 and 2016, a phylogenetic study was made of 121 pectolytic soft rot bacteria isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…It should be emphasised that, in this study, we have detected the presence of the same Pectobacterium and Dickeya species on asymptomatic vegetables and ornamental plants as those which occurred on plants with disease symptoms in the same countries from which we have analysed samples (Brasil, Egypt, Morocco, UK, USA, Israel, Finland, Norway, the Netherlands and Poland) [3,12,17,18,21,[40][41][42][43][44][45][46][47][48][49][50][51]. In addition, the presence of virulent strains of the same species of Pectobacterium and Dickeya has been described in the rivers of Finland [45] and France [39].…”
Section: Discussionmentioning
confidence: 94%
“…It should be emphasised that, in this study, we have detected the presence of the same Pectobacterium and Dickeya species on asymptomatic vegetables and ornamental plants as those which occurred on plants with disease symptoms in the same countries from which we have analysed samples (Brasil, Egypt, Morocco, UK, USA, Israel, Finland, Norway, the Netherlands and Poland) [3,12,17,18,21,[40][41][42][43][44][45][46][47][48][49][50][51]. In addition, the presence of virulent strains of the same species of Pectobacterium and Dickeya has been described in the rivers of Finland [45] and France [39].…”
Section: Discussionmentioning
confidence: 94%
“…While only a limited number of strains have been sequenced for D. aquatica, D. lacustris or D. poaceiphila, D. dianthicola is a good example of species homogeneity as all 33 analyzed strains of this species belong to the Vfm genetic group I (Fig. 2, Table S1), as well as the 16 recently sequenced strains (data not shown, Curland et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…They largely secrete pectate lyases to degrade the plant cell wall pectin, leading to the dissociation and maceration of the plant tissues (Hugouvieux-Cotte-Pattat et al, 2014). Of specific concern are three Dickeya species: D. solani provoking emergent damages in potato fields, particularly in Europe, resulting in its classification as a quarantine organism in Israel and Ireland (Toth et al, 2011), whereas D. dianthicola causes severe losses in potato production in the United States (Curland et al, 2021) and D. oryzae provokes significant losses in rice fields in China (Lv et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It was found in Pakistan [ 13 ] and Morocco [ 14 ]. In 2016, it caused a severe outbreak in the US [ 15 , 16 ] and, in 2017, in Western Australia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…MLSA analyses based on housekeeping gene sequences showed that little sequence diversity was found in D. dianthicola strains [ 8 , 12 , 16 , 18 , 19 , 20 ]. This high relatedness was confirmed by whole-genome analyses [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%